miR-135b-3p Promotes Cardiomyocyte Ferroptosis by Targeting GPX4 and Aggravates Myocardial Ischemia/Reperfusion Injury - Sun, Weixin; Shi, Ruijie; Guo, Jun; Wang, Haiyan; Shen, Le; Shi, Haibo; Yu, Peng; Chen, Xiaohu (Frontiers in Cardiovascular Medicine, 2021)
Ferroptosis is a form of cell death induced by excess iron and accumulation of reactive oxygen species in cells. Recently, ferroptosis has been reported to be associated with cancer and ischemia/reperfusion (I/R) injury in multiple organs. However, the regulatory effects and underlying mechanisms of myocardial I/R injury are not well understood. The role of miR-135b-3p as an oncogene that accelerates tumor development has been confirmed; however, its role in myocardial I/R is not fully understood. In this study, we established an in vivo myocardial I/R rat model and an in vitro hypoxia/reoxygenation (H/R)-induced H9C2 cardiomyocyte injury model and observed that ferroptosis occurred in tissues and cells during I/R myocardial injury. We used database analysis to find miR-135b-3p and validated its inhibitory effect on the ferroptosis-related gene glutathione peroxidase 4 (Gpx4), using a luciferase reporter assay. Furthermore, miR-135b-3p was found to promote the myocardial I/R injury by downregulating GPX4 expression. The results of this study elucidate a novel function of miR-135b-3p in exacerbating cardiomyocyte ferroptosis, providing a new therapeutic target for improving I/R injury.